Evaluation of a non-Gaussian puff model. (1st January 2001) - Tirabassi, T.; Mangia, C.; Rizza, U.; Degrazia, G.A.
This paper presents the evaluation of a model based on a general technique for solving the K-equation using the truncated Gram-Charlier expansion (type A) of the concentration field and a finite set of the equations for the corresponding moments. The model can be applied routinely using simple ground-level meteorological data acquired by an automatic network as input. A performance evaluation is shown in the case of continuous emission from an elevated source in a variable boundary layer.